Managing Labour in Small Firms - Marlow, Susan; Patton, Dean; Ram, Monder; Marlow, Susan; Patton, Dean; Ram, Monder (Taylor & Francis, 2005)
The majority of employees currently working in the private sector are now employed in small firms, yet little is known about their working conditions. This collection of essays addresses this gap. Based on theoretical analysis supported by contemporary empirical evidence, the book explores key areas of the employment relationship adding a new perspective to our understanding of contemporary work.
English
Keywords: Business & management; Entrepreneurship; Management & management techniques; Research & development management; employment; relations; sector; relationship; effort; wage; bargain; unfair; dismissal; act